Modelling viscous behaviour of clayey geomaterials using single mechanical-analogue model - Nor Shahidah Mohd Nazer (Penerbit Universiti Kebangsaan Malaysia, 2019)
The design of sustainable early warning systems for landslide prone areas requires deep understanding of the kinematic of landslides with emphasis on the evolution of its movement. This is controlled by many factors, and creep is a major one. Creep is perceptively slow land sliding process where the movement is nearly imperceptible and occurring at a rate of millimetres (mm) per year. This article reports the results of investigations of the viscous shear behaviour of clayey geo-materials, in particular creep and relaxation, which were carried out using a direct shear box. The viscous behaviour was investigated by either measuring the decay in shear stress at constant relative horizontal displacement (stress relaxation test) or by measuring the evolution of relative horizontal displacements at constant shear stress (creep test). Initially, 3 elements model of spring and dashpots combination was proposed to simulate the viscous behaviour of clayey geo-materials. However, because the loading system of direct shear box is not stiff and is showing some creep/relaxation interplay during viscous test, effect from the compliance system of the shear box must be carefully considered when formulating mechanical models for saturated and unsaturated slope kinematics. Another elastic element was added to the 3 elements model to address the issue of deforming loading system. The proposed modified model capable of simulating creep and stress relaxation response using a single set of parameters and thus, allowing creep response to be inferred from stress relaxation response by means of direct shear test in lab.